2023
DOI: 10.3390/en16041643
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Recovery from Livestock Manure Digestate through an Air-Bubble Stripping Reactor: Evaluation of Performance and Energy Balance

Abstract: The recovery of livestock manure, rich in nutrients, as fertilizer in agriculture, could pose the risk of an excessive load of nitrogen on the soil. Ammonia stripping is one of the available technologies for reducing the amount of nitrogen in the digestate obtained by the anaerobic digestion of manure. The study investigated the performance and energy consumption of a full-scale ammonia-stripping plant, equipped with a bubble reactor and working without the use of any alkaline reagent under semi-batch conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Table 3 shows the effect of AS on the final characteristics of DRS and DD after 24 h of Test 1. As it is possible to observe from Figure 1, PA gradually decreased along the treatment for both DRS and DD, while the IA of DRS remained higher than 6000 mg CaCO 3 L −1 after 24 h. The PA decrease allowed for CO 2 stripping, thus reducing the bicarbonate and carbonate ion content and the buffer capacity of the matrix [13,21]. CO 2 volatilization led to an increase in pH [11] and to a shift in the ammonia dissociation equilibrium (NH 4 + ↔ NH 3 + H + ), which depends on pH and temperature, towards the free ammonia nitrogen (FAN) production [31].…”
Section: Air Stripping Efficiency On Raw Cattle Slurry and The Liquid...mentioning
confidence: 87%
See 1 more Smart Citation
“…Table 3 shows the effect of AS on the final characteristics of DRS and DD after 24 h of Test 1. As it is possible to observe from Figure 1, PA gradually decreased along the treatment for both DRS and DD, while the IA of DRS remained higher than 6000 mg CaCO 3 L −1 after 24 h. The PA decrease allowed for CO 2 stripping, thus reducing the bicarbonate and carbonate ion content and the buffer capacity of the matrix [13,21]. CO 2 volatilization led to an increase in pH [11] and to a shift in the ammonia dissociation equilibrium (NH 4 + ↔ NH 3 + H + ), which depends on pH and temperature, towards the free ammonia nitrogen (FAN) production [31].…”
Section: Air Stripping Efficiency On Raw Cattle Slurry and The Liquid...mentioning
confidence: 87%
“…According to the specific aim, an AS tower could precede the AD reactor or come in succession. Nevertheless, AS could be affected by the formation of fouling during the process and elevated energy and chemical requirements for an increase in pH [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several technologies have been tested to recover ammonium from livestock manure, such as nutrient chemical precipitation in the form of struvite [2,3], water evaporation [4,5], the use of hydrophobic membranes [6][7][8] and other mostly emergent technologies, e.g., bioelectrochemical systems [9,10]. One of the most extended technologies for ammonia recovery is air stripping and absorption [11][12][13]. This process is based on the ammoniumammonia equilibrium (Reaction (1)).…”
Section: Introductionmentioning
confidence: 99%
“…In this process, ammonia is removed from the liquid fraction by flowing air through the bulk. This technology has been successfully applied to digestate [17][18][19], landfill leachate [20,21], and wastewater [22]. Alkali addition may be required in order to raise the pH and optimize the process, which involves expenses for the chemicals [23].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these technologies have some limitations, such as the consumption of energy for heating the digestate, alkali to adjust the pH, scaling and fouling (due to the formation of calcium carbonate on the surface of packing materials), which can affect ammonia removal efficiencies over time [16,24]. To overcome some of these disadvantages, alternative technologies such as jet loop and aero-cyclone reactors [24], semi-batch jet loop reactors [26], water spray reactors [27], and air bubble reactors [18,28] are being implemented and studied. In particular, bubble reactors have the main advantage of not being sensitive to fouling, and it has been demonstrated that, working under sufficiently high temperature (above 60 • C), the dosage of alkaline reagents may be prevented [18].…”
Section: Introductionmentioning
confidence: 99%